Determinants of electronic documentation of patient data among nurses at Dr. Batta General Military Hospital, Entebbe, Wakiso District. A cross-sectional study. - Nalubega, Jane Frank; Muhwezi, Peter; Nansereko Hasifa, Nansereko Hasifa; Naggulu, Immaculate Prosperia (Student's Journal of Health Research Africa, 2025)
Background The integration of Electronic Health Records into healthcare systems is vital for improving documentation accuracy, care coordination, and patient safety. However, the adoption of electronic documentation by nurses in Uganda remains low. This study aimed to assess the individual and health facility-related determinants influencing the use of electronic documentation among nurses at Dr. Batta General Military Hospital, Entebbe. Methodology A descriptive cross-sectional study was conducted using structured self-administered questionnaires with a sample of 30 nurses selected through simple random sampling. Data were analyzed using descriptive statistics and presented in tables, bar graphs, and pie charts. Results The majority of respondents were aged 26–31 years (40.0%) and predominantly female (66.7%). Most nurses (83.3%) correctly understood the meaning of electronic documentation, and 60% had received prior training. However, key individual barriers included lack of skills or confidence (50.0%), fear of making mistakes (33.3%), and system complexity (33.3%) as the main reasons for non-use. On the health facility side, 56.7% of respondents reported insufficient electronic equipment, 63.3% indicated the absence of clear documentation guidelines, and 56.7% stated they lacked adequate support and supervision. Conclusion Electronic documentation among nurses is hindered by limited digital competence, resistance to change, inadequate refresher training, and negative perceptions. Institutional barriers such as poor infrastructure, weak leadership, and a lack of clear policies further exacerbate the challenge. Without addressing these barriers, the hospital risks continued inefficiencies in patient data management and care delivery. Recommendations The Ministry of Health should invest in targeted ICT and EHR training programs to boost nurses’ skills and confidence. Dr. Batta General Military Hospital must strengthen its technological infrastructure and provide consistent technical support. Hospital administration should simplify EHR systems and establish clear documentation policies to improve usability and compliance.